The Effect of Debt to Equity Ratio, Dividend Payout Ratio, and Earnings Growth on Price to Earnings Ratio in Indonesia's Mining Sector - Ayudhasurya, De Rembulan; Murtaqi, Isrochmani (Journal of Business and Management, 2012)
Investors play an important role in corporate sustainability. To make investors trust and be confident in investing, a company has to have good responsibility to them, especially in reporting the condition of financial performance. One of the analysis that investors will consider in the financial performance is price earnings ratio (PER). It shows how much money investor paid per share relative to the company’s net income. Investors’ willingness to invest in a company can be measured by calculating the price earnings ratio.This research is conducted to examine whether debt to equity ratio, dividend payout ratio, and earnings growth affect price earnings ratio in mining companies in Indonesia, both in Badan Usaha Milik Negara (BUMN) companies and in private companies. The data is secondary data that is collected from the annual report of the companies. The sample in this analysis is 7 mining companies that are listed in Jakarta Stock Exchange during a five-year period, from 2007 until 2011. The analysis is calculated by using multiple linear regression to test the influence of independent variables to the dependent variables. The significance influence test for hypothesis of independent variables is using T-test and F-test with 5% level of significant.Keywords: price to earnings ratio, debt to equity ratio, dividend payout ratio, earnings growth, indonesia’s mining companyCategory: Finance